Influencia de la red social Instagram en la imagen corporal de adolescentes de un colegio de la ciudad de Guadalajara de Buga (2023)
This research project proposes as its main objective to examine the effect of the social network Instagram on the body perception of teenagers from a school in Guadalajara de Buga. The specific objectives include identifying the use of Instagram and its impact on the body image of these teenagers, as well as describing the relationship between self-image and the impact of Instagram on their body perception.